Conflict and human African trypanosomiasis - Berrang-Ford, Lea; Lundine, Jamie; Breau, Sebastien (Social science & medicine (1982), 2011)
Human African Trypanosomiasis (HAT) has reemerged in sub-Saharan Africa as a disease of major public health importance. The success of HAT elimination in sub-Saharan Africa is subject to the feasibility of controlling, eliminating, or mitigating the determinants of incidence in affected countries. Conflict has been widely recognized and cited as a contributing factor to the resurgence of HAT in many countries, as well as to continuing HAT incidence in politically unstable and resource-poor regions. Despite extensive anecdotal and qualitative recognition of the role of conflict, there has been no quantitative research of this topic at the population level in affected African countries. We characterize the qualitative and quantitative associations between HAT incidence and conflict-related processes in HAT-affected African countries over the past 30 years. HAT and conflict-related data were collected for 35 affected countries in sub-Saharan Africa for the years 1976–2004. Descriptive and univariate inferential statistics, as well as negative binomial regression modeling, are used to assess the associations between HAT and conflict. A space-time scan statistic is used to identify significant incidence clusters. Clusters of HAT incidence over the past 30 years have predominantly coincided with periods of conflict or socio-political instability. HAT cases occurred significantly more often in countries and during years with conflict, high political terror, and internationalized civil war. The results indicate a lag period between the start of conflict events and a peak in incidence of approximately 10 years. We recommend explicit consideration and quantification of socio-political measures such as conflict and terror indices in GIS (Geographic Information Systems)-based risk assessments for HAT policy and intervention.